1984
DOI: 10.1177/030006058401200314
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Appraisal of Flucloxacillin in the Management of Skin and Soft Tissue Infections in Nigeria

Abstract: The resolution of skin and soft tissue infections following a single course of treatment with flucloxacillin was assessed in 235 patients recruited by nineteen physicians. In all, 88.5% of patients were completely cured or showed a highly satisfactory improvement after 3 to 12 days' treatment. Only three patients failed to show any improvement at all. Side-effects were limited to twelve patients (5.1%) all of whom were able to complete their course of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…A previous publication (from our hospital) on flucloxacillin plasma concentration in children (Bergdahl et al 1986) reports no difference in plasma concentration when the compound was administered to fasting infants or together with food. Doses lower than those in this study have successfully been used in treatment of staphylococcal infections in children (Price & Harding 1975;Duncan 1984).…”
Section: Discussionmentioning
confidence: 93%
“…A previous publication (from our hospital) on flucloxacillin plasma concentration in children (Bergdahl et al 1986) reports no difference in plasma concentration when the compound was administered to fasting infants or together with food. Doses lower than those in this study have successfully been used in treatment of staphylococcal infections in children (Price & Harding 1975;Duncan 1984).…”
Section: Discussionmentioning
confidence: 93%
“…According to bacteriological data in the literature, authors have shown that most cases of pyoderma are caused by S. pyogenes in several tropical developing settings, 1,2,9–12 and therefore narrow‐spectrum penicillins might be the most appropriate candidates for standard treatment. Mass or selective treatment with intramuscular benzathine‐penicillin has been recommended during epidemics of poststreptococcal glomerulonephritis, 9,13 but, apart from this specific situation, very few therapeutic trials for pyoderma in a tropical environment are available; furthermore, published studies have largely focused on potential second‐line drugs such as cotrimoxazole or flucloxacillin, 14,15 or costly drugs that are seldom available in developing countries such as topical mupirocin or fusidic acid 16,17 ; in addition, none of those trials has been comparative.…”
Section: Introductionmentioning
confidence: 99%
“…Infected lesions of the skin, such as boils, carbuncles and cellulitis, are common reasons for patients to seek a consultation in general practice 1 , the great majority of bacterial skin and soft tissue infections being due to pathogenic streptococci and staphylococci 2 . Infected skin lesions are frequently treated with oral antibiotics, penicillin being the drug of choice for many years.…”
Section: Introductionmentioning
confidence: 99%